Citogenética molecular comparativa do DNAr 18S e 5S em piranhas (Serrasalminae, Characidae) da Amazônia Central - Nakayama, Celeste Mutuko (2007)
Basic and molecular cytogenetic studies have been performed in 11 species of the subfamily Serrasalminae: Colossoma macropomum, Serrasalmus (S. altispinnis, S. elongatus, S. gouldingi, S. rhombeus, S. cf rhombeus, S. serrulatus and S. maculatus), Pygocentrus nattereri, Pristobrycon striolatus and Catoprion mento, collected along different sites in Central Amazon basin. The diploid number found was 2n=54 chromosomes in Colossoma macropomum, 2n=62 in C. mento and P. striolatus, 2n=60 for all species in the genus Serrasalmus and P. nattereri, except for S. cf. rhombeus, which presented 2n=58. Besides distinct diploid numbers, variable karyotypical formulae were also detected, even between species with the same chromosomal number, showing the occurrence of chromosomal rearrangements in the evolutionary process of this group, such as fusions and centric fisions and pericentric inversions. No sex chromosome heteromorphism was found in the analyzed species. The silver stained nucleolus organizer regions (Ag-NORs) were always telomeric and multiple, ranging from 4 to 12 marks according to each species. In most species, they were observed on short arms of subtelo-acrocentric chromosomes. However, in Colossoma macropomum the Ag-NORs were located at terminal position on long arms and, in Catoprion mento, they were present on short ams of submetacentric chromosomes and on long arms of subtelocentric and acrocentric chromosomes. The 18S rDNA sites were usually coincident with Ag-NORs, although they might occur in a higher number or in distinct chromosomes positions in relation to Ag-NORs. These discrepancies may be attributed to either methodological specificities or to difficulties in detecting some NOR sites, since they are commonly very small within Serrasalminae. The C-banded heterochromatin was observed at pericentromeric region of most chromosomes, being some regions more conspicuous than others, besides some telomeric bands in some chromosomal pairs. All Serrasalmus species presented a proximal heterochromatic block on the long arm of a medium-sized metacentric pair, which seems to be a marker for this genus regarding to its karyotype position (7th pair), once it may be present in other species, such as P. nattereri, but in a larger chromosome (3rd pair). The 5S rDNA sequences were always mapped in a single chromosomal pair. In Serrasalmus species, this pair corresponds to the metacentric pair 7 and in P. nattereri, P. striolatus and C. mento, it corresponds to the medium-sized metacentric pair 3. On its turn, the 5S rDNA sites in C. macropomum were located on short arms of a small metacentric, probably corresponding to the 12th pair. Considering the wide array of the present data, the species of the genera Serrasalmus, Pygocentrus, Pristobrycom and Catoprion, in spite of their specific differentiations, showed higher karyotypic similarity with the presence of metacentric, submetacentric, subtelocentric and acrocentric chromosomes, a preferential location of 18S rDNA sites at telomeric region on short arms of subteloacrocentric chromosomes, besides the number and location of 5S rDNA sites in karyotypes. On the other hand, C. macropomum shows quite divergent features, with 2n=54 meta-submetacentric chromosomes, with 18S rDNA sites at terminal region on long arms and interstitial 5S rDNA sites on short arms of chromosomes. Therefore, the location of C. macropomum far from the piranha clades, according to available phylogeny hypotheses for Serrasalminae, is corroborated by our cytogenetic data. Considering that C. macropomum would be a basal representative in the phylogeny of Serrasalminae, chromosomal rearrangements such as centric fissions, besides pericentric inversions, seem to play an important role in the karyotypic differentiation of this group, increasing the basal number of 2n=54 meta-submetacentric to 2n=58, 60 and 62, and giving rise to distinct chromosome forms in relation to those present in C. macropomum. Analogously, the NOR sites have also undergone numerical and positional changes in chromosomes along the karyotypical differentiation of Serrasalminae. As for the 5S rDNA sites, its location in a same position in morphologically similar chromosomes in all analyzed species of the genera Serrasalmus, Pygocentrus, Pristobrycom and Catoprion suggests that, once established this location from a distinctive ancestor condition, as that seen in C. macropomum, it has been remained conserved.